London 2012 - Keen, P. (5. International Forum on Elite Sport. Beijing, China, 3-6 September 2007, 2007)
UK 2012 Performance Strategy: 1. Research the performance path from talent recognition to Olympic Podium 2. Agree the highest attainable goal given the time available 3. Estimate the number of athletes of sufficient calibre required to establish successful athlete pathways 4. Specify the performance staff, infrastructure and operational costs needs to operate these 5. A logic for maximising the number of medals and medallists from the whatever budget is available 6. Specify the essential national framework, central systems and services needed to pull it all together